2014
DOI: 10.1001/jamasurg.2013.4823
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Age and Mortality After Liver Transplant

Abstract: Morphometric age correlated with mortality after liver transplant with better discrimination than chronologic age. Assigning a morphometric age to potential liver transplant recipients could improve prediction of postoperative mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 14 publications
1
54
0
1
Order By: Relevance
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported the cross-sectional muscle area with corresponding skeletal muscle index (12)(13)(14)17,(22)(23)(24)(25)30), whereas the psoas area was reported in eight studies (15,16,18,19,21,(26)(27)(28) and the dorsal muscle group area was reported in one study (20). One study calculated the morphometric age (calculated with total psoas area, psoas density, and abdominal aortic calcifications) (29). The mean skeletal muscle index ranged from 43.0 to 54.3 cm²/m² (13,30).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations